Why silver deposition is so fast: Solving the enigma of metal deposition - Pinto, Leandro M. C. [UNESP]; Spohr, Eckhard; Quaino, Paola; Santos, Elizabeth; Schmickler, Wolfgang (Wiley, 2013)
A perfect match: Silver deposition is one of the fastest electrochemical reactions, even though the Ag+ ion loses more than 5 eV solvation energy in the process. This phenomenon, an example of the enigma of metal deposition, was investigated by a combination of MD simulations, DFT, and specially developed theory. At the surface, the Ag+ ion experiences a strong interaction with the sp band of silver, which catalyzes the reaction. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: corrosion; metal deposition; theoretical electrochemistry; Electrochemical reactions; MD simulation; Metal deposition; Perfect matches; Silver deposition; Solvation energy; Strong interaction; Catalysis; Chemistry; Corrosion; Deposition